Salience of Image Areas with the Greatest Increase in Total Contrast - V. V. Babenko; D. V. Yavna; L. A. Migunova (Neuroscience and Behavioral Physiology, 2026)

Carbon dynamics in termite mounds: The effect of land use on microbial oxalotrophy - Teneille Nel; Catherine E. Clarke; Michele L. Francis; Darya Babenko; Alf Botha; Daniel O. Breecker; Don A Cowan; Timothy Gallagher; Pedro Lebre; Joseph R. McAuliffe; Alyssa N. Reinhardt; Marla Trindade (CATENA, 2025)

The metastable associations of bacteriophages and Erwinia amylovora - Natalya V. Besarab; Maria A. Letarova; Vladislav V. Babenko; Ilya S. Belalov; Alla K. Golomidova; Eugene E. Kulikov; Alexander L. Lagonenko; Anatoly N. Evtushenkov; Andrey V. Letarov (Archives of Microbiology, 2023)

Two novel Erwinia amylovora bacteriophages, Loshitsa2 and Micant, isolated in Belarus - Natalya V. Besarab; Andrey V. Letarov; Eugene E. Kulikov; Vladislav V. Babenko; Ilya S. Belalov; Alexander L. Lagonenko; Alla K. Golomidova; Anatoly N. Evtushenkov (Archives of Virology, 2022)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Differentially Expressed Genes of the Slc6a Family as Markers of Altered Brain Neurotransmitter System Function in Pathological States in Mice - V. N. Babenko; D. A. Smagin; I. L. Kovalenko; A. G. Galyamina; N. N. Kudryavtseva (Neuroscience and Behavioral Physiology, 2020)

Effects of Bariatric Surgeries on the Size of Myocardial Infarction and Ghrelin Level in Rats with Experimental Decompensated Type 2 Diabetes Mellitus - O. V. Kornyushin; D. L. Sonin; Ya. G. Toropova; E. I. Pochkaeva; G. V. Semikova; O. M. Berko; I. A. Zelinskaya; N. M. Todosenko; L. S. Litvinova; A. E. Neimark; A. Yu. Babenko; K. V. Dergach; et al. (Bulletin of Experimental Biology and Medicine, 2019)

Heterogeneity of Brain Ribosomal Genes Expression Following Positive Fighting Experience in Male Mice as Revealed by RNA-Seq - Dmitry A Smagin; Irina L Kovalenko; Anna G Galyamina; Yuriy L Orlov; Vladimir N Babenko; Natalia N Kudryavtseva (Molecular Neurobiology, 2018)

Protection of Neurovascular Unit Cells with Lithium Chloride and Sodium Valproate Prevents Brain Damage in Neonatal Ischemia/Hypoxia - D. N. Silachev; E. Yu. Plotnikov; V. A. Babenko; E. S. Savchenko; L. D. Zorova; I. B. Pevzner; M. V. Gulyaev; Yu. A. Pirogov; G. T. Sukhikh; D. B. Zorov (Bulletin of Experimental Biology and Medicine, 2016)

Intra-Arterial Administration of Multipotent Mesenchymal Stromal Cells Promotes Functional Recovery of the Brain After Traumatic Brain Injury - D. N. Silachev; E. Yu. Plotnikov; V. A. Babenko; T. I. Danilina; L. D. Zorov; I. B. Pevzner; D. B. Zorov; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2015)